Effect of Center-Pivot Irrigation Intensity on Groundwater Level Dynamics in the Agro-Pastoral Ecotone of Northern China - Lian, Jie; Li, Yulin; Li, Yuqiang; Zhao, Xueyong; Zhang, Tonghui; Wang, Xinyuan; Wang, Xuyang; Wang, Lilong; Zhang, Rui (Frontiers in Environmental Science, 2022)
Groundwater-based irrigation is an effective buffer against water disconnects during droughts in areas of intensive agriculture. However, it is difficult to implement effective measures to sustainably utilize aquifers due to the unclear understanding of irrigation intensity in the agro-pastoral ecotone. To explore the influence of regional irrigation intensity on groundwater level (GL), we investigated the dynamics of Kernel density for irrigation well from 2000 and the changed GL (ΔGL in three groups) in a typical center-pivot irrigation (CPI) area (about 1,000 km2). The results showed that the implementation of CPI systems caused a rapid land-use change from natural grassland (NG) to cultivated pasture (CP). The observed ΔGL in deeper group (0.63 m yr−1, GL > 20 m) was significantly (p < 0.05) higher than that in shallower group (0.38 m yr−1, GL < 10 m) and medium group (0.43 m yr−1, 10 m < GL < 20 m). The predicted ΔGL and GL were significantly and positively correlated with the CPI well density (R2 = 0.447 and 0.429, p < 0.001), respectively, and showed a fitted plane function based on the variables (R2 = 0.655, p < 0.001). It indicted that the intensive cropping in the agro-pastoral ecotone profoundly changed regional irrigation intensity, resulting in a rapid response of the GL. To reduce the risk of increased irrigation costs and ensure sustainable availability of groundwater, it’s necessary to control the density of CPI systems in hotspot areas, and implement water-saving measures to balance water usage and recharge rates for sustainable groundwater management.